THE INFLUENCE OF BRAND EQUITY AND PRICE ON CONSUMER PURCHASE INTENTIONS OF EIGER OUTDOOR EQUIPMENT IN KARAWANG REGENCY - Alifia, Putri; Ratnasari, Ina (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study aims to examine and analyze the influence of brand equity and price on consumer purchase intentions of Eiger outdoor equipment in Karawang Regency. Brand equity is considered one of the important factors influencing purchase decisions, while price is often a primary consideration for consumers when choosing a product. The research method used is descriptive quantitative. The sample in this study consisted of 400 respondents using purposive sampling as the sampling technique. Data analysis was conducted using SPSS software, and the analytical techniques used included reliability testing, descriptive analysis, t-tests, and multiple linear regression analysis. The results showed that brand equity has a positive and significant influence on consumer purchase intentions. This is indicated by a positive and significant regression coefficient at a 95% confidence level. Price also has a significant influence on purchase intentions. Overall, brand equity and price simultaneously have a significant influence on the purchase intentions of Eiger outdoor equipment in Karawang Regency